PERSPEKTIF HUKUM ISLAM TERHADAP PERKAWINAN SIRI BAGI PRAJURIT TNI TERHADAP ISTRI KEDUA (Studi Kasus Perkara Putusan No. 17-K PM.III-16/AD/I/2020) - Agung Prama Sarno Agung; Asni; Siti Nurul Fatimah (Universitas Islam Negeri Alauddin Makassar)
This research includes field research or Qualitative Field Research. The research is obtained from primary data sources and legislation. The approach used in this research is a syar'i juridical and empirical approach. The results of this study indicate that sitting in the case in this decision, that is, it is legally and convincingly proven to violate the 1st Criminal Code Article 279 paragraph (1), with the impact that the second wife does not get a living from the defendant but the child from the marriage continue to earn a living because it is the defendant's obligation based on Law Number 35 of 2014 amendments to Law number 23 of 2002 concerning child protection. In Islamic law a marriage can be carried out as long as it fulfills the requirements and pillars that have been explained, without any recording by the State, while in the decision No.17-K PM.III-16/AD/I/2020 and in the trial process there were witnesses. who is a guardian or witness in the consent process but in other cases, the defendant hides his identity regarding the defendant who already has a legal wife and is registered by the State.